QUAD ZYGOMATIC IMPLANT AS REHABILITATION IN POST MUCORMYCOSIS PATIENTS: A CASE SERIES - Sohini Gupta; Dr Vikas Kunwar Singh; Dr Ruchika Tiwari; Dr Prashansa Gaikwad; Dr Hardik Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: Mucormycosis is an opportunistic fungal infection, which primarily affects diabetic and immunocompromised patients. Surgical excision and debridement of the affected areas can result in significant defects. Reconstruction and rehabilitation of these defects remains a significant challenge for the clinicians.Case series: In this case series, we present 3 cases of post mucormycosis patients with maxillary defect who underwent rehabilitation by quad zygomatic implants. No complications occurred during the follow up.  Discussion: There are several choices for maxillary reconstruction, such as maxillary prostheses, local and regional pedicled flaps with and without bone grafts, and titanium mesh. Soft-tissue flaps do not provide bony reconstruction of maxillary defects or structural support for osseo-integrated implants hence the quad zygoma proves to be a good treatment choice for treating maxillary defects. The main advantage of patients opting for zygomatic implant is that there is no need for adjunctive surgeries thereby considerably reducing overall treatment duration and cost. Zygomatic implants are fixed into the zygoma and they can be immediately loaded with a temporary prosthesis, followed by a fixed prosthesis after four to six months.Conclusion: All the patients were followed up after 15, 30, 45 and 90 days and there after every month for evaluation of soft tissue healing, infection, dehiscence, loosening of prosthesis, eating efficiency and aesthetic. Follow-up period for all 3 patients was in the range of 6-12 months. The design of zygoma implants allows the surgeons to insert these implants even in case of total maxillary bone defect because they obtain a bicortical stability through the malar bone. Zygomatic implants have, in many cases, shown improved clinical results compared with bone grafting and represent a possible new ‘gold-standard’ procedure in compromised maxillary bone.